Analysis of bodybuilder`s skeletal muscle characteristics using tensiomyography - Hoon Chai, J.; Kyeong Kim, B.; Kim, C.; Hyun Kim, C.; Won Bae, S. (The Korean Journal of Sports Medicine, 2016)
The aim of this study is to evaluate the contractile properties of thigh muscles in bodybuilders through tensiomyography (TMG). Our hypothesis is that maximal displacement (Dm) in bodybuilders would be lower than in controls because Dm is increased when the muscle is stiffed or hypertrophied. Nine bodybuilder athletes and 15 university students were assessed by TMG. The biceps femoris (BF), semitendinosus (ST), vastus lateralis, vastus medialis (VM), and rectus femoris (RF) were evaluated. The TMG parameters obtained for each muscle were Dm, contraction time (Tc). And we calculated contraction velocity (Vc) as the rate of the radial displacement occurring during the time period of Tc with respect to Tc. Dm values of all muscles in bodybuilders were significantly higher compared to the control group. There were no significant differences in Tc values of most muscles except right BF and ST muscles. Vc values of VM, RF, and ST muscles were lower in bodybuilders than in the control group. This is the first report about TMG assessment of muscle hypertrophy. We found that Dm was most effective in detecting muscle hypertrophy and muscle stiffness secondary to muscle hypertrophy could induce decrease in Dm and Vc.